Characteristics of lake sturgeon Acipenser fulvescens Rafinesque, 1817 in a tributary of Lake Michigan, USA: Status of the Muskegon River population. (11th April 2017) - Harris, B. S.; Ruetz, C. R.; Wieten, A. C.; Altenritter, M. E.; Smith, K. M.
Summary: The overall goal of this study was to characterize the age, growth, condition, and total catch of lake sturgeon Acipenser fulvescens in a remnant population associated with a Lake Michigan, USA tributary. Lake sturgeon were captured (2008–2013) using large‐mesh (25.4 and 30.5 cm) and small‐mesh (6.4 and 7.6 cm) gill netting in Muskegon Lake (which connects the Muskegon River to Lake Michigan), and adults were captured with boat electrofishing in the Muskegon River. A total of 268 unique lake sturgeon (24.8–191.0 cm total length; <0.1–59.5 kg weight) were captured. Of these, 180 fish were aged using pectoral fin rays, representing 27 age cohorts and a mean age of 7.6 years. The weight–length relationship for lake sturgeon was log10 ( W ) = 3.446·log10 ( L ) − 6.163 and the von Bertalanffy growth model was L = 180.719 [1−e −0.093( t + 0.902) ], where W was wet weight (kg), L was total length (cm), and t was age (years). Mean growth rate of juveniles (ages 3–6) recaptured in successive years was 8.6 cm/year and 558 g/year. Annual catch of adults during the spawning migration suggested that the number of spawners each year was low (i.e., probably <50 individuals in most years). Natural reproduction appeared to be occurring given the catch of juvenile lake sturgeon in Muskegon Lake. However, recovery of this remnant population is uncertain given the population age structure and low rate of adult recruitment during the study.